A novel high-altitude electromagnetic pulse (HEMP) protection circuit for RF applications. (February 2019) - Hao, Ruirong; Zhang, Xiaodong; Gao, Huai; Wu, Haodong; Cheng, Jianchun; Li, Guann-Pyng
Abstract: A High-Altitude Electromagnetic Pulse (HEMP) protection circuit with ultra-low loading capacitance for RF applications that does not degrade RF circuit performances is proposed. Principle of operation, loading capacitance, leakage current, EMP clamping characteristics and robustness over transient over-voltage pulse will be presented. As a case study, a 5.8 GHz WLAN InGaP/GaAs hetero-junction bipolar transistor (HBT) power amplifier with this compact EMP protection circuit is demonstrated. The test result shows that the EMP protection circuit can provide 18 kV contact discharge per IEC 61000−4−2 standard without degradation in PA performances.